Carbon Quantum Dots with Ultra-High Quantum Yield for Versatile Turn-On Sensor of Gluten and Cyanide Ions - Melo-Freire, R (Elsevier Ltd, 2024)
In this work, we reported the synthesis of carbon quantum dots (CQDs) with high fluorescent quantum yield (90.7 %). These nanoparticles were applied in a turn-off/turn-on sensor able to detect cyanide ions. In this sensing strategy, Fe3+ ions were added to the aqueous suspension of CQDs to quench the fluorescence of the system, which was recovered from the presence of cyanide ions. Furthermore, a sensor array was developed using the LDA chemometric tool, to classify different species present in cookie formulations, including gluten. The turn-off/turn-on sensor proved to be sensitive and effective for detecting cyanide ions, with a detection limit of 3.77 ppm. This high sensibility and selectivity allowed quantifying the analyte in a real sample of tap water. © 2024 Elsevier Ltd